Comparison of U.S. Environmental Protection Agency's CAP88 PC Versions 3.0 and 4.0. (August 2015) - Jannik, Tim; Farfan, Eduardo B.; Dixon, Ken; Newton, Joseph; Sailors, Christopher; Johnson, Levi; Moore, Kelsey; Stahman, Richard
Abstract : Abstract: The Savannah River National Laboratory (SRNL) with the assistance of Georgia Regents University, completed a comparison of the U.S. Environmental Protection Agency's (U.S. EPA) environmental dosimetry code CAP88 PC V3.0 with the recently developed V4.0. CAP88 is a set of computer programs and databases used for estimation of dose and risk from radionuclide emissions to air. At the U.S. Department of Energy's Savannah River Site, CAP88 is used by SRNL for determining compliance with U.S. EPA's National Emission Standards for Hazardous Air Pollutants (40 CFR 61, Subpart H) regulations. Using standardized input parameters, individual runs were conducted for each radionuclide within its corresponding database. Some radioactive decay constants, human usage parameters, and dose coefficients changed between the two versions, directly causing a proportional change in the total effective dose. A detailed summary for select radionuclides of concern at the Savannah River Site ( 60 Co, 137 Cs, 3 H, 129 I, 239 Pu, and 90 Sr) is provided. In general, the total effective doses will decrease for alpha/beta emitters because of reduced inhalation and ingestion rates in V4.0. However, for gamma emitters, such as 60 Co and 137 Cs, the total effective doses will increase because of changes U.S. EPA made in the external ground shine calculations.